Los controles contables y su incidencia en la contabilidad del Servicentro L.L. de propiedad del señor Ángel León López de la ciudad de Machala. - Rojas Torres, Cecibel del Cisne (2013)
This thesis develops the theme entitled "Accounting controls and their impact on accounting Servicentro L.L. owned by Mr. Ángel León López Machala city ". The research allowed us to identify the main problems was the Servicentro L.L. owned by Mr. Ángel López León through techniques and research tools studied throughout my college career and thus to raise a proposal to provide a solution to the problems mentioned above. This research is structured in five chapters which are detailed below: Chapter I: This chapter is drawn problematic situation of the organization and why it was possible to run the investigation in order to resolve it, additionally indicate the rationale and objectives; Chapter II: This chapter develops the theoretical framework, which covers the background research, the legal reasoning, research on the concepts of dependent and independent variables of the problem raised and pointing out the hypothesis; Chapter III: This chapter develops the research methodology, which contains the basic mode of research, population and sample that would account for the development of research techniques; Chapter IV: This chapter performed the analysis and interpretation of the results found in the observation, staff interviews and business surveys to accountants in the province, to verify the hypothesis presented in Chapter II; Chapter V: This chapter concludes the investigation raising the solution to the problem by developing a proposal, the same design is based on a manual audit to enable sound decision making by management. This thesis will be of considerable importance because it will allow us to solve the problems that are common in all companies of individuals required to keep accounting, the main problems are detected in these businesses are: the lack of instructional procedures , the lack of inventory control and account control inefficient cash and cash equivalents.